Investigating the Self-Perception of Social, Emotional, and Academic Inclusion of Students with and without Special Educational Needs through Photovoice - Alexandra Pirker; Julia Hafenscher; Katharina-Theresa Lindner (MDPI AG, 2023)
Several studies have investigated the perceptions of inclusion by students with special educational needs (SEN) and without SEN, most of them quantitatively. This research aims to expand the understanding of the perceived inclusion of students through qualitative interviews by examining how emotions, social relationships, and academic concepts matter. Therefore, the photovoice method was used for data collection, followed by semi-structured interviews, which were analyzed according to Mayring's Qualitative Content Analysis. Regarding social integration in the classroom, the results of the interviews with six students with SEN and three students without SEN show mainly positive experiences with their classmates and attach great importance to school spaces (e.g., the schoolyard) that are used for interaction and communication among each other. In terms of the teacher-student relationship, it becomes apparent that the students place particular value on the support and help of the teachers in everyday school life as well as in private matters. Some students' statements indicate that the self-perception of their academic self-concept differs in various school subjects. A contrast of perception between the students with and without SEN was not detected. Concerning emotional inclusion, the students primarily expressed statements related to emotion regulation and individual adaption strategies.